Yoga vs. static stretching: Recovery impact on male athletes` post-HIIT heart rate, respiratory rate, blood pressure, and heart rate variability analysis - Petviset, H.; Pakulanon, S.; Rusmeeroj, S.; Rukdang, B. (International Journal of Exercise Science, 2024)
Heart rate and heart rate variability indicate an athlete's cardiovascular recovery and autonomic balance after intense exercise. While stretching aids recovery, its effects on autonomic balance are inconsistent. Yoga`s combination of postures, breathing, and relaxation may further activate the parasympathetic system, making it a promising tool for sports recovery. This study employed a crossover design to examine the effects of yoga and stretching on post 30-min session of high-intensity interval training (HIIT) recovery in male athletes. Twenty athletes of Mae Fah Luang University (Age 20.95±0.99 years old, VO2max 42.53±4.79 ml/kg/min) were given recovery methods, 15-min stretching and 15-min yoga following HIIT. Heart rate, blood pressure, respiratory rate, and heart rate variability were evaluated immediately after HIIT, 5-min, 10-min, 15-min of the recovery period, and at 24-hour after recovery. A Two-way repeated-measures analysis of variance (ANOVA) was employed to examine the interaction effects between different methods and time of recovery. A significance level of 0.05 indicated a statistically significant difference. The findings indicated a statistically significant interaction between the group and time of heart rate variability and respiratory rate (p<0.05, effect size [ES] medium). Post-hoc analysis indicated that performing yoga showed a significantly lower respiratory rate at 5-min, 10-min, and 15-min compared to stretching (p<0.05, ES large). Yoga demonstrated a noteworthy enhancement in heart rate variability during the 5-min and 10-min recovery periods in comparison to stretching. In summary, this study provides empirical evidence supporting the efficacy of yoga as a post-exercise recovery strategy following high-intensity interval training. The role of breathing, rhythmic muscle contractions, and deep relaxation in yoga appears to facilitate the recovery phase more effectively than stretching alone. This suggests incorporating yoga as an active recovery regimen.